Interview with André Leonardo Chevitarese: a new look at the study of the Historical Jesus and the Paleo-Christianity - Chevitarese, André Leonardo (Romanitas - Revista de Estudos Grecolatinos, 2013)
Interview with André Leonardo Chevitarese.
Keywords: Interview; André Leonardo Chevitarese; Historical Jesus; Paleo-Christianity